2004
DOI: 10.1002/crat.200310193
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the investigation of orientation relationships in meteoritic plessite

Abstract: The orientation relationship (OR) between the bcc and fcc phase in the plessite microstructure of the iron meteorites Watson, Agpalilik and Gibeon has been analysed in a scanning electron microscope using electron back-scattered diffraction (EBSD). A very strong OR exists, independently on the analysed plessite type and the observed spreading of single orientation data. The agreement between the experimental orientation distribution and existing models varies for each meteorite. The black plessite in the Agpal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Please note, that the left cluster shows the same orientation as the surrounding large kamacite crystal. This behaviour of plessite has been already reported in [26] on the Gibeon meteorite.…”
Section: Local Phase Characterizationmentioning
confidence: 54%
See 2 more Smart Citations
“…Please note, that the left cluster shows the same orientation as the surrounding large kamacite crystal. This behaviour of plessite has been already reported in [26] on the Gibeon meteorite.…”
Section: Local Phase Characterizationmentioning
confidence: 54%
“…In [26] it was shown that plessite similarly presents the same OR as detected for the Widmanstätten macrostructure.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…1 obtained on a 9% Cr steel. Similar features appear in many fcc-bcc martensitic materials such as CuZn brasses [3], bainitic steels [4] and FeNi meteorites [5][6][7]. They are not artefacts that could be attributed to the EBSD method, as Bunge et al also observed them by synchrotron X-ray diffraction [8].…”
Section: Introductionmentioning
confidence: 83%
“…Kurdjumow-Sachs [9] The determination of the OR can be realized either by filtering the PFs [5,6] or by more complex calculations [4]. Most of the time, the singular features around the averaged OR are simulated by a superposition of NW and KS ORs [13,14] or by a higher number of discrete ORs including NW, KS, GT and other intermediate ORs [7].…”
Section: Introductionmentioning
confidence: 99%